2011
DOI: 10.1007/s10100-011-0229-0
|View full text |Cite
|
Sign up to set email alerts
|

Credit rating analysis using adaptive fuzzy rule-based systems: an industry-specific approach

Abstract: This paper presents an analysis of credit rating using fuzzy rule-based systems. The disadvantage of the models used in previous studies is that it is difficult to extract understandable knowledge from them. The root of this problem is the use of natural language that is typical for the credit rating process. This problem can be solved using fuzzy logic, which enables users to model the meaning of natural language words. Therefore, the fuzzy rule-based system adapted by a feed-forward neural network is designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The input attributes were collected for U.S. companies in the year 2008, while the output financial performance (Z-score) was evaluated for the year 2010, and the change in the financial performance was measured as Z-score in 2010 related to its value in 2008. Following previous studies (Hajek 2012), we excluded the companies from the mining and financial industries to prevent problems with both industry-specific attributes and different financial performance evaluation. As a result, we were able to collect data for 448 U.S. companies, 199 of them classified into "safe zone", 172 classified into the "grey zone", and 44 into the "distress zone" category.…”
Section: Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The input attributes were collected for U.S. companies in the year 2008, while the output financial performance (Z-score) was evaluated for the year 2010, and the change in the financial performance was measured as Z-score in 2010 related to its value in 2008. Following previous studies (Hajek 2012), we excluded the companies from the mining and financial industries to prevent problems with both industry-specific attributes and different financial performance evaluation. As a result, we were able to collect data for 448 U.S. companies, 199 of them classified into "safe zone", 172 classified into the "grey zone", and 44 into the "distress zone" category.…”
Section: Data Descriptionmentioning
confidence: 99%
“…have been applied to predict future financial distress. These approaches have evolved from the use of univariate and multivariate statistical models (Altman 1968) to recent use of artificial intelligence (AI) methods such as neural networks (NNs) (Wilson, Sharda 1994;Hajek 2011;Cimpoeru 2011), support vector machines (SVMs) (Huang et al 2004;Hajek, Olej 2011), decision trees (Hajek, Michalak 2013), fuzzy rule-based systems (Chen et al 2011;Hajek 2012), or evolutionary algorithms (Varetto 1998). Comparative reviews of the modes can be found in Bellovary et al (2007), Ravi Kumar and Ravi (2007), or Kirkos (2012).…”
mentioning
confidence: 99%
“…Evolutionary algorithms have shown promising results for other generalizations of FISs [33,34,35]. Finally, we recommend future studies on related problems such as credit rating prediction [36].…”
Section: The Case Of Corporate Bankruptcy Predictionmentioning
confidence: 97%
“…A wide range of AI methods have been applied to predict credit ratings, including statistical classifiers [3], decision trees [1], neural networks (NNs) [4], [5], support vector machines (SVMs) with both supervised [6], [7] and semi-supervised learning [8], case-based reasoning [9], artificial immune systems [10], rough sets [11], fuzzy rule-based systems (FRBSs) [12], and ensemble approaches [10], [13]. Recent efforts have also indicated that AI methods should be integrated into the feature selection process to improve prediction accuracy [1].…”
Section: Introductionmentioning
confidence: 99%